Impact of a digital medicine programme on hepatitis C treatment adherence and efficacy in adults at high risk for non‐adherence. Issue 12 (30th April 2020) - Sulkowski, Mark; Luetkemeyer, Annie F.; Wyles, David L.; Martorell, Claudia; Muir, Andrew; Weisberg, Ilan; Gordon, Stuart C.; McLain, Richard; Huhn, Gregory
Summary: Background: Direct‐acting anti‐virals (DAA) are highly effective for hepatitis C virus (HCV) treatment, but perceived risks of medication non‐adherence may restrict access to care. Digital medicine programme (DMP) has improved adherence and outcomes for some conditions. Aims: To conduct a prospective, single‐arm, open‐label study across the United States to assess the impact of DMP on adherence and efficacy in adults with chronic HCV infection at high risk for non‐adherence. Methods: Eligible participants were placed on the DMP to evaluate real‐time adherence; primary outcome was sustained virological response (SVR) at ≥10 weeks post‐treatment. Results: Between August 2017 and April 2019, 288 participants (Medicaid, 64.9%; psychiatric disorders, 61.1%; homeless, 9.4%) received DAAs for 8‐12 weeks (sofosbuvir/velpatasvir or ledipasvir, 45%; glecaprevir/pibrentasvir, 55%). SVR was achieved in 99.1% of 218 participants who had HCV RNA assessed at ≥10 weeks post‐treatment; of the 70 participants who did not have SVR assessed, 17 had SVR4 with HCV RNA assessed at a median (IQR; interquartile range) 5.6 weeks (4.1, 7.9) post‐treatment; one completed treatment but did not have HCV RNA assessed, and 52 discontinued treatment early without assessment. Overall, the primary analysed participants (n = 218) actively used the DMP for median (range) 92.9% (12.5%, 100%) of their prescribed treatment time, and overall pill‐taking adherence was 95.0% (57.1%, 100%). Participants reported the programme was useful and easy to use through satisfaction surveys. Conclusions: HCV treatment with DMP was accepted by patients and clinicians and may support HCV treatment outcomes among patients at high risk for treatment non‐adherence (Clinical trials.gov NCT03164902).